Primary antibody deficiency: The impact on the quality of life and mental health of affected children and their parents. (25th January 2021) - Berg, Annika Klungland; Diseth, Trond H.; Abrahamsen, Tore Gunnar; Halvorsen, Kathleen; Reinfjell, Trude; Erichsen, Hans Christian
Abstract: Aim: To evaluate health‐related quality of life, mental health and treatment‐related stress responses in children with primary antibody deficiency and both their parents. Methods: Children and their parents completed the standardised questionnaires Pediatric Quality of life Inventory, Strength and Difficulties Questionnaire and Impact of Event Scale. Parents also completed standardised questionnaires regarding their own mental health and quality of life. The results were compared to those of healthy children, kidney transplanted children and children in remission from acute lymphoblastic leukaemia. Results: Children with primary antibody deficiency reported a poorer health‐related quality of life compared to healthy children and children in remission from acute lymphoblastic leukaemia. They reported poorer mental health compared with healthy children. Mothers of children with primary antibody deficiency reported poorer mental health compared to mothers of healthy children but comparable to mothers of chronically ill children. Parents reported a similar quality of life as the general Norwegian population. Treatment with subcutaneous immunoglobulin infusions at home is generally well tolerated, but some report severe treatment‐related stress. Conclusion: Primary antibody deficiency has a significant impact on quality of life and mental health of affected children. Patients and parents with severe treatment‐related stress should be identified and helped.